Systematic Review: The Hidden Impact of Workplace Loneliness and Its Organizational Remedies - Abdul Rahman Ibrahim; Ghitsna Nadila Farha (Jurnal Psikologi dan Konseling West Science, 2025)
Workplace loneliness has emerged as a significant issue affecting employees’ well-being and organizational performance. This study systematically reviews recent empirical literature on workplace loneliness. Using a PRISMA 2020-based Systematic Literature Review (SLR), 530 articles were retrieved from Scopus and Google Scholar, and eight met the inclusion criteria. Results indicate that workplace loneliness reduces work engagement, organizational commitment, and job satisfaction while increasing emotional exhaustion. However, supervisor support, coworker exchange, empathic leadership, and resilience mitigate its negative impact. The novelty of this study lies in synthesizing recent studies (2020–2024), offering practical implications for developing inclusive human resource policies.